Pendidikan Toleransi Dalam Keluarga Beda Agama: Sebuah Pendampingan Keindonesiaan - Harisantoso, Imanuel Teguh; Toding, Randing Rante (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2025)
This article aims to describe and analyze tolerance education in interfaith families from the perspective of Indonesian assistance. Indonesian assistance aims to develop abilities and quality of life as well as increase the dignity of the Indonesian people. This is based on the religious and socio-cultural values ​​of Indonesian society. This article is qualitative in nature with a reflective-analytical thinking approach. The data used in this research comes from previous research which discusses the harmonious life of families of different religions. The results of the research found that tolerance education in families of different religions reflects Indonesian support. In this educational practice, relationships of friendship, mutual cooperation, brotherhood, solidarity and an attitude of sharing are obtained. This forms a harmonious and inclusive family based on a concrete understanding and practice of tolerance